A Cost Analysis of Nursing Activities for COVID-19 Patient Screening at the Acute Respiratory Infection Clinic (ARI) in a Tertiary Hospital - Pamornpun , Chutima; Singchungchai, Phechnoy; Chatdokmaiprai, Kannikar (Nursing Journal CMU, 2022)
The objective of this descriptive research was to analyze the cost of nursing activities for COVID-19 patient screening at the acute respiratory infection clinic in a tertiary hospital. The target population included all personnel cost reports, and the subject group was 30 COVID-19 patient screening cost reports selected using purposive sampling. Three research instruments were used: 1) cost records for nursing activities regarding COVID-19 patient screening, 2) a dictionary of nursing activities, and 3) records of nursing activity cost drivers. The content validity index of all the research instruments was 1, and the Inter-observer reliability was 0.8. Data were analyzed with descriptive statistics, including frequency, percentage, mean, and standard deviation. It was found that the total cost of nursing activities was 73,877.55 baht with the highest cost of nursing care before screening (23,891.68 baht; 32.34%), followed by the cost of nursing administration and supporting activities (23,889.15 baht; 32.33%). When analyzing cost per activity, it was found that the activity of nursing care before screening had the highest cost at 108.60 baht, and the cost per case was 2,462.58 baht with the highest cost per case being nursing care before screening at 796.39 baht. This research indicates that nursing activity cost analyses for COVID-19 patient screening is considered new, and the empirical data should be used by nursing administrators for the management of resources, manpower, time, and budget planning to achieve more efficiency and increase nursing care quality in preparation for future emerging infectious diseases.